Hierarchical FeCoP nanosheets array anchored on phenolic resin derived N-doped porous carbon as a high-efficiency bifunctional electrocatalyst for alkaline water splitting - Qin Wang; Jiaxin Pei; Xiaoya Wei; Yangyang Li; Hongxin Li; Jiangyong He; Bi Chen; Jian Li; Yu Meng; Long Yan (Fuel, 2027)

Phytochemical profiling of Manglietia chevalieri and its potential in attenuating pulmonary fibrosis: Insights into bioactive constituents - Zi-Jie Long; Mao-Mao Zheng; Yu-Hang He; Bi-Xi Tang; Zhi-Xuan Wang; Xian-Neng Lu; Xi Chen; Jia Li; Yi Zang; Juan Xiong (Phytochemistry, 2027)

Effects of Hericium erinaceus powder incorporation on gluten interactions, water-state distribution, starch digestibility and quality characteristics of wheat noodles - Yu-Ling Yang; Chao Yang; Long Yang; Zhang-Jie Bi; Chang-Qing Dong; Xue-Bin Yin; Ze-Xuan Gong; Zhi-Peng Liu; Ke Bian (Food Research International, 2026)

Constructing a “switch” for photo-thermal catalytic pathway: Directional regulation of NO reduction product distribution by the coordination mode at the La site over Pd–La/CeO2 - Jianfei Li; Boxiang Du; Qian Xia; Zhuoran Bi; Xiangyu Meng; Jinlin Long; Zizhong Zhang; Wenxin Dai; Xianzhi Fu (Chemical Engineering Journal, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Machine learning prediction and analysis for LFL of C0-C2 combustible gases and blends under wide operating conditions - Mingkun Zhang; Wenchao Zhu; Dan Shen; Xiangyu Meng; Wuqiang Long; Mingshu Bi (Journal of Cleaner Production, 2026)

The green innovation effect of environmental regulations: a quasinatural experiment based on China’s consumption tax policy on batteries and coatings - Chang Liu; Feng Long; Xue Tian; Fenfen Bi; Zhuyi Chen; Xiao Li (Environment, Development and Sustainability, 2026)

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

The transcription factor WRKY1 is involved in decreasing the contents of citric acid during postharvest storage of blueberry fruits - Lei Sun; Siyu Long; Wanjiao Zhu; Jiayang Bi; Xin Zhou; Qian Zhou (Postharvest Biology and Technology, 2026)

Cinnamaldehyde alleviates LPS-induced endoplasmic reticulum stress-mediated barrier damage in IPEC-J2 by regulating calcium homeostasis - Tian-Hao Wang; Zhou-Yi Yang; Bi-Chen Zhao; Kanwar Kumar Malhi; Qing Zhang; Jian-Jie Li; Feng-Qiu Nie; Zhong-Fang Zhou; Li-Jian Shi; Chun-Jiang Wang; Jin-Long Li (Chemico-Biological Interactions, 2026)

A Mid-Pleistocene Provenance Shift in the Bohai Strait at 0.94 Myr: Implications for Synergistic Controls on Yellow River Integration - Wei Xiong; Xi Mei; Long Huang; Naishuang Bi; Zongzhu Han; Yong Zhang; Zhonglei Wang (Journal of Ocean University of China, 2026)

Zircon–monazite geochronology and zircon Hf–O isotopes of Ediacaran–Cambrian paragneiss from the Mashan Complex, Jiamusi Block, NE China: implications for sedimentary–metamorphic–tectonic evolution - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Zheng Ji; Yan-Long Zhang; Jun-Hui Bi; Wen-Chun Ge (International Geology Review, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Two distinct patterns for advanced simultaneous nitrogen and phosphorus removal treating low C/N wastewater in a low DO anaerobic/oxic/anoxic-aerobic granular sludge (AOA-AGS) system - Jingwei Ma; Ying Han; Yaning Ji; Hui Sun; Peng Bi; Long Chen; Xinrui Zhang; Xinru Li; Shiquan Ren; Liang Zhu; Qiulai He (Environmental Research, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Convergent enrichment of core functional guilds involved in Fe-N metabolism in anammox and activated sludge: Insights into genome-resolved metagenomics - Hui Sun; Ying Han; Shiquan Ren; Xinrui Zhang; Xinru Li; Peng Bi; Long Chen; Liang Zhu; Guangchao Yang; Jingwei Ma; Qiulai He (Bioresource Technology, 2026)

Solidago canadensis alters rhizosphere bacterial communities of Artemisia argyi under warming and nitrogen deposition—invaded rhizospheres become similar to the invader's - Yong-Feng Wang; Yun-Long Zhang; Ying Li; Guang-Qian Ren; Shan-Shan Qi; Bi-Ying Zhao; Zhi-Cong Dai; Dao-Lin Du (Plant and Soil, 2026)

Effect of S, N co-doped carbon-based supports on low-temperature NH3-SCR: Resistance to SO2, H2O and denitrification mechanism - Shuangshuang Yan; Dongmei Bi; Shiyan Sun; Hui Wang; Xiang Zhu; Long Wang; Shanjian Liu (Journal of Environmental Chemical Engineering, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

Seismic performance of beam-column joints reinforced with ECC - Long Liu; Hongbo Xiao; Songqiang Wan; Chunling Yan; Yu Wang; Chong Liu; Xiaoze Yang; Liang Cui; Chenjie Hao; Menghao Ming; Boyang Liu; Yingying Bi (Bulletin of Earthquake Engineering, 2026)

Directional Hydraulic Fracturing in Lushan Shale: Effects of Stress Magnitude and Pre-crack Angle on Fracture Propagation - Anfa Long; Yongfa Zhang; Yu Zhao; Shengfeng Wu; Chaolin Wang; Jing Bi; Huasen Huang; Kai Wang (Rock Mechanics and Rock Engineering, 2026)

Niche differentiation drives microbial community assembly in an anaerobic/oxic/anoxic-aerobic granular sludge (AOA-AGS) system: Insights into Anammox self-enrichment - Jingwei Ma; Hui Sun; Yaning Ji; Qiulai He; Long Chen; Ying Han; Peng Bi; Liang Zhu (Water Research, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Enhancing anaerobic methane production from corn straw: Promoting lignocellulosic biomass biodegradation via aeration in liquid fraction of digestate for green and efficient pretreatment - Bi-Long Chen; Ting-Ting Zhang; Aqsa Arooj; Cheng Xu; Jia-Cheng E. Yang; Mika Sillanpää; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

A cellulose-based near-infrared fluorescent probe for ratiometric imaging and visual monitoring of ClO− in water via smartphone - Wei Bi; Chuanli Ren; Yuxin Xiao; Feng Wang; Qingmao Long; Yanfei Lin; Xinjie Yang; Li Liu; Lianpeng Zhang; Guanben Du (Environmental Research, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

Balancing water efficiency and crop productivity: rhizosphere microbiome shifts in drought-resistant rice - Junguo Bi; Jiayi Li; Saeed ur Rahman; Yuchong Long; Nan Hui; Martin Romantschuk; Junqiang Zheng; Xianxian Zhang; Danping Hou; Jinsong Tan; Qingyu Bi; Hui Xia; et al. (World Journal of Microbiology and Biotechnology, 2025)

Integration of partial nitrification, endogenous denitrification and anaerobic ammonia oxidation in low dissolved oxygen anaerobic/oxic/anoxic-aerobic granular sludge reactor treating low carbon to nitrogen ratios wastewater - Jingwei Ma; Long Chen; Yaning Ji; Hui Sun; Ying Han; Liang Zhu; Peng Bi; Qiulai He (Bioresource Technology, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Advanced low C/N wastewater treatment in an AOA-AGS sequencing batch reactor via aerobically stimulating simultaneous nitrification and denitrification - Jiyi Chen; Long Chen; Yang Liu; Jingwei Ma; Weihong Wu; Xiang Wang; Yaning Ji; Yuhong Wen; Peng Bi; Hui Sun; Ying Han; Xinrui Zhang; et al. (Journal of Water Process Engineering, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Electro-cultivation of hydrogen-oxidizing bacteria to promote ammonia resource recovery and microbial protein synthesis in microbial electrolysis cell - Jingwei Ma; Long Chen; Qiulai He; Hui Sun; Ying Han; Liang Zhu; Peng Bi (Chemical Engineering Journal, 2025)

Re-understanding Sedimentary Characteristics of Shallow-water Delta in Funing Formation, Gaoyou Sag, Subei Basin, Eastern China - Zi-yi Yang; Gui-yu Dong; Lian-bo Zeng; Tian-zhuo Bi; Yong-feng Qiu; Hao Li; Xu Yang; Wen-long Qian; Mehdi Ostadhassan (Applied Geophysics, 2025)

Predicting the Height of Water-Conducting Fissure Zones in a Jurassic Coalfield Based on AdaBoost-WOA-BPNN - Enke Hou; Meng Bi; Tianwen Long; Xiaoshen Xie; Pengfei Hou; Qianlong Li (Mine Water and the Environment, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Functional divergence of CAD-like family genes in Saccharum complex under biotic and abiotic stress - Zhu-Qing Wang; Sheng-Ren Sun; Hao-Yu Wang; Zheng-Wang Bi; Hai-Long Chang; Shuo-Hang Zhang; Jun-Lv Chen; Yuan-Xia Qin; Jian-Tao Wu; Wei Zhang; Huan-Ying Xu; San-Ji Gao; et al. (Plant Cell Reports, 2025)

Fecal microbiota transplantation: transitioning from chaos and controversial realm to scientific precision era - Xinjun Wang; Di Zhao; Dexi Bi; Long Li; Hongliang Tian; Fang Yin; Tao Zuo; Gianluca Ianiro; Ning Li; Qiyi Chen; Huanlong Qin (Science Bulletin, 2025)

Chemical kinetic study of lean-burn and NO/N2O behaviors on ethanol/ammonia cracked gas - Xiangyu Meng; Menglan Miao; Xuanrui Zhang; Yuqiang Li; Wuqiang Long; Mingshu Bi (Science of The Total Environment, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Effective inactivation of Trichothecium roseum spores in apple juice using contact glow discharge electrolysis: Applications and mechanisms - Haitao Long; Lumei Pu; Yongcai Li; Yuhong Xu; Weibing Xu; Huali Xue; Yang Bi (Food Research International, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Hot syngas cleanup for pilot two-stage fluidized bed steam-oxygen biomass gasification plant - Zhijie Fu; Nazanin Charchi Aghdam; Sahand Nekoeian; Jing He; Long Cheng; Shida Liu; Lei Zhang; Junnan Chao; Xiaoyang Wei; Ruixu Wang; Bhavya Nagda; Yumeng Zhang; et al. (Bioresource Technology, 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Quaternary transgression process controlled by tectonic subsidence over the last 1.35 Ma: New insights from the eastern Bohai Sea - Wei Xiong; Long Huang; Yong Zhang; Zhonglei Wang; Nai Shuang Bi; Jun Pan; Jun Sun; Lelong He; Feifei Wang; Xi Mei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effect of sequential fermentation with indigenous non-Saccharomyces cerevisiae combinations and Saccharomyces cerevisiae on the chemical composition and aroma compounds evolution of kiwifruit wine - Wangsheng Sun; Xiaowen Chen; Sinuo Feng; Pengfei Bi; Jia Han; Shiqi Li; Xu Liu; Zhe Zhang; Fangyu Long; Jing Guo (Food Chemistry, 2024)

Creep mechanism of landslide formation in rock with bedding and weak layers in Zezhou, Shanxi, China - Zhiqiang Yi; Jianhui Long; Wenhui Shi; Hongyan Yan; Jining Zhang; Wenjun Bi; Yuqi Jin (Bulletin of Engineering Geology and the Environment, 2024)

Moldy odors in food - a review - Di Gong; Dov Prusky; Danfeng Long; Yang Bi; Ying Zhang (Food Chemistry, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Simultaneous inoculation of non-Saccharomyces yeast and lactic acid bacteria for aromatic kiwifruit wine production - Wangsheng Sun; Sinuo Feng; Pengfei Bi; Jia Han; Shiqi Li; Xu Liu; Zhe Zhang; Fangyu Long; Jing Guo (Food Microbiology, 2024)

A dual-action Rhein-peptide hydrogel synergistically inhibits inflammation and matrix degradation for therapeutic mitigation of abdominal aortic aneurysm - Mingliang Wang; Yaling Li; Yizhou Bai; Zien Lin; Shenghui Bi; Yunxiang Long; Yanbin Cai; Xiaowu Wang (Chemical Engineering Journal, 2024)

Hybrid neural network wind speed prediction based on two-level decomposition and weighted averaging - Qi Bi; Yu-long Bai; Zai-hong Hou; Rui Wang (Earth Science Informatics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

The migration and volatilization of toxic elements during briquette pyrolysis procedure - Juan Chen; Jianjun Wu; Yixin Zhang; Yang Guo; Long Yan; Jian Li; Zhenkun Guo; Bi Chen; Hua Wang (Minerals Engineering, 2024)

Characterization of the effect of non-Saccharomyces cerevisiaes on the non-volatile constituents and volatile profiles of low-alcoholic pomegranate beverages - Pengfei Bi; Wangsheng Sun; Shiqi Li; Xu Liu; Yuhan Tian; Fangyu Long; Zhe Zhang; Jing Guo (Food Bioscience, 2024)

Screening and characterization of indigenous non-Saccharomyces cerevisiae with high enzyme activity for kiwifruit wine production - Wangsheng Sun; Xiaowen Chen; Pengfei Bi; Jia Han; Shiqi Li; Xu Liu; Zhe Zhang; Fangyu Long; Jing Guo (Food Chemistry, 2024)

Study on ammonia/methanol blends with ammonia cracking for low-carbon combustion and NO reduction - Xiangyu Meng; Lizi Liu; Meichao Qin; Menglan Miao; Hang Zhao; Wuqiang Long; Mingshu Bi (Journal of Cleaner Production, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

The effect of microgroove pattern modification combined with MOF coating on titanium alloy for the soft tissue integration of percutaneous implants - Baobao Xue; Sheng Miao; Yue Yuan; Wenbo Geng; Donglin Li; Chao Yang; Jiahao Zeng; Kaiyong Cai; Hongbo Wei; Long Bi; Junjun Fan (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Analysis of forestry management based on dynamic life cycle assessment of biogenic carbon: A case study of a forestry resource-based city in Northeast China - Bo Song; Jin Tang; Feng Long; Yuqing Peng; Fenfen Bi; Yueao Kang; Dayi Qian (Journal of Cleaner Production, 2024)

Visualization and simulation study of ammonia blending with hydrogen as combustion application in lean-burn condition - Xiangyu Meng; Meichao Qin; Lizi Liu; Fuxing Wei; Jiangping Tian; Wuqiang Long; Mingshu Bi (Fuel, 2024)

Combined effects of bedding anisotropy and matrix heterogeneity on hydraulic fracturing of shales from Changning and Lushan, South China: An experimental investigation - Yongfa Zhang; Yu Zhao; Anfa Long; Chaolin Wang; Jing Bi (Journal of Asian Earth Sciences, 2024)

Quaternary-ammonium chitosan, a promising packaging material in the food industry - Yu-Long Qiu; Yixi Li; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Carbohydrate Polymers, 2024)

Efficient degradation of ciprofloxacin by a flower-spherical Bi2MoO6/BiOCl Z-type heterojunction photocatalyst enriched with oxygen vacancies - Juanqin Xue; Wen Xiao; Long Shi; Yujie Liu; Peng Wang; Qiang Bi (Journal of Environmental Chemical Engineering, 2023)

Amino carboxymethyl chitosan//dialdehyde starch/polyvinyl alcohol double-layer film loaded with ε-polylysine - Xiaoxia Chen; Yixi Li; Yu-Long Qiu; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Food Chemistry, 2023)

Investigation of ammonia cracking combined with lean-burn operation for zero-carbon combustion and NO/N2O/NO2 improvements - Xiangyu Meng; Meichao Qin; Lizi Liu; Zechuan Cui; Jiangping Tian; Wuqiang Long; Mingshu Bi (Journal of Cleaner Production, 2023)

Age-specific difference in the temporal relationships between updated cardiovascular health construct and arterial stiffness in middle-aged and older adults - Jiaojiao Huang; Xiaoli Xu; Yingxia Zhou; Zhuojun Xin; Qiuyu Cao; Ruixin He; Tianzhichao Hou; Yi Ding; Jieli Lu; Tiange Wang; Zhiyun Zhao; Yu Xu; et al. (GeroScience, 2023)

Efficient pyridine biodegradation by Stenotrophomonas maltophilia J2: Degradation performance, mechanism, and immobilized application for wastewater - Hongyu Niu; Zimeng Nie; Yu Long; Jiayuan Guo; Ju Tan; Junping Bi; Haijun Yang (Journal of Hazardous Materials, 2023)

Efficient methotrexate adsorption on magnetic-functionalised UiO-66-NH2: Selectivity, mechanisms and recycling - Qiang Bi; Bo Yang; Kun Zhang; Tong Yang; Peng Wang; Long Shi; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

A novel Transformer-based network forecasting method for building cooling loads - Long Li; Xingyu Su; Xianting Bi; Yueliang Lu; Xuetao Sun (Energy and Buildings, 2023)

Toward efficient deep learning system for in-situ plankton image recognition - Junbai Yue; Zhenshuai Chen; Yupu Long; Kaichang Cheng; Hongsheng Bi; Xuemin Cheng (Frontiers in Marine Science, 2023)
Plankton is critical for the structure and function of marine ecosystems. In the past three decades, various underwater imaging systems have been developed to collect in-situ plankton images and image processing has been a major bottleneck that hinders the deployment of plankton imaging systems. In recent years, deep learning methods have greatly enhanced our ability of processing in-situ plankton images, but high-computational demands and longtime consumption still remain problematic. In this study, we used knowledge distillation as a framework for model compression and improved computing efficiency while maintaining original high accuracy. A novel inter-class similarity distillation algorithm based on feature prototypes was proposed and enabled the student network (small scale) to acquire excellent ability for plankton recognition after being guided by the teacher network (large scale). To identify the suitable teacher network, we compared emerging Transformer neural networks and convolution neural networks (CNNs), and the best performing deep learning model, Swin-B, was selected. Utilizing the proposed knowledge distillation algorithm, the feature extraction ability of Swin-B was transferred to five more lightweight networks, and the results had been evaluated in taxonomic dataset of in-situ plankton images. Subsequently, the chosen lightweight model and the Bilateral–Sobel edge enhancement were tested to process in-situ images with high level of noises captured from coastal waters of Guangdong, China and achieved an overall recall rate of 91.73%. Our work contributes to effective deep learning models and facilitates the deployment of underwater plankton imaging systems by promoting both accuracy and speed in recognition of plankton targets.

Involvement of the heat shock response (HSR) regulatory pathway in cadmium-elicited cerebral damage - Milton Talukder; Shao-Shuai Bi; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2023)

Immobilization of chromium in real tannery sludge via heat treatment with coal fly ash - Yonglin Yang; Shuaige Shi; Chao Zhu; Xiangping Chen; Yongyong Hao; Long Yan; Jian Li; Xiaodong Chen; Bi Chen; Xiangrong Ma; Hongrui Ma (Chemosphere, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Meyerozyma guilliermondii promoted the deposition of GSH type lignin by activating the biosynthesis and polymerization of monolignols at the wounds of potato tubers - Xiaoyuan Zheng; Xuejiao Zhang; Jinmei Zhao; William Oyom; Haitao Long; Ruirui Yang; Lumei Pu; Yang Bi; Dov Prusky (Food Chemistry, 2023)

In silico cell factory design driven by comprehensive genome-scale metabolic models: development and challenges - Jiangong Lu; Xinyu Bi; Yanfeng Liu; Xueqin Lv; Jianghua Li; Guocheng Du; Long Liu (Systems Microbiology and Biomanufacturing, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

Artificial intelligence technologies in bioprocess: Opportunities and challenges - Yang Cheng; Xinyu Bi; Yameng Xu; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Bioresource Technology, 2023)

Understanding of combustion characteristics and NO generation process with pure ammonia in the pre-chamber jet-induced ignition system - Xiangyu Meng; Chenhan Zhao; Zechuan Cui; Xiaolei Zhang; Mingkun Zhang; Jiangping Tian; Wuqiang Long; Mingshu Bi (Fuel, 2023)

Cerebellar injury induced by cadmium via disrupting the heat-shock response - Shao-Shuai Bi; Milton Talukder; Xue-Tong Sun; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2022)

Cadmium Through Disturbing MTF1-Mediated Metal Response Induced Cerebellar Injury - Shao-Shuai Bi; Milton Talukder; Hai-Tao Jin; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Neurotoxicity Research, 2022)

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Genomic characterizations of H4 subtype avian influenza viruses from live poultry markets in Sichuan province of China, 2014–2015 - Chuansong Quan; Ting Huang; Xiuwei Chen; Jie Zhang; Qianli Wang; Cheng Zhang; Tiyan Zhang; Lijun Zhou; Liumei Shu; Chunrong Long; Lei Yang; Xunbo Du; et al. (Science China Life Sciences, 2018)

Distribution and controlling factors of phytoplankton assemblages associated with mariculture in an eutrophic enclosed bay in the East China Sea - Yuanzi Huo; Zhangliang Wei; Qiao Liu; Fangfang Yang; Lijuan Long; Qi Zhang; Hongsheng Bi; Qing He; Peimin He (Acta Oceanologica Sinica, 2018)

Genome-wide study refines the quantitative trait locus for number of ribs in a Large White × Minzhu intercross pig population and reveals a new candidate gene - Long-Chao Zhang; Jing-Wei Yue; Lei Pu; Li-Gang Wang; Xin Liu; Jing Liang; Hua Yan; Ke-Bin Zhao; Na Li; Hui-Bi Shi; Yue-Bo Zhang; Li-Xian Wang (Molecular Genetics and Genomics, 2016)

Programmed cell death in the cyanobacterium Microcystis aeruginosa induced by allelopathic effect of submerged macrophyte Myriophyllum spicatum in co-culture system - Yan He; Qiao-Hong Zhou; Bi-Yun Liu; Long Cheng; Yun Tian; Yong-Yuan Zhang; Zhen-Bin Wu (Journal of Applied Phycology, 2016)

Hepatitis E virus infection activates signal regulator protein α to down-regulate type I interferon - Fen Huang; Chenchen Yang; Wenhai Yu; Yanhong Bi; Feiyan Long; Jue Wang; Yunlong Li; Shenrong Jing (Immunologic Research, 2016)

Plant regeneration from shoot regrowth and de novo embryo-like structures from cryopreserved shoot tips of Lilium spp. - Wen-Lu Bi; Zhen-Fang Yin; Liang Guo; Long Chen; Chen Pan; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

An efficient, widely applicable cryopreservation of Lilium shoot tips by droplet vitrification - Zhen-Fang Yin; Wen-Lu Bi; Long Chen; Bing Zhao; Gayle M. Volk; Qiao-Chun Wang (Acta Physiologiae Plantarum, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

Direct shoot regeneration from basal leaf segments of Lilium and assessment of genetic stability in regenerants by ISSR and AFLP markers - Zhen-Fang Yin; Bing Zhao; Wen-Lu Bi; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2013)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

Relating hydrograph components to rainfall and streamflow: a case study from northern Taiwan - Yu-Ji Li; Shin-jen Cheng; Tsang-Long Pao; Yi-jie Bi (Hydrological Sciences Journal, 2012)

Mineral status and mechanical properties of cancellous bone exposed to hydrogen peroxide for various time periods - Dan Li; Long Bi; Guolin Meng; Jun Wang; Rong Lv; Min Liu; Jian Liu; Yunyu Hu (Cell and Tissue Banking, 2011)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Detoxification of Gramine by the Cereal Aphid Sitobion avenae - Qing-Nian Cai; Ying Han; Ya-Zhong Cao; Yuan Hu; Xin Zhao; Jian-Long Bi (Journal of Chemical Ecology, 2009)

Constitutive and Induced Activities of Defense-Related Enzymes in Aphid-Resistant and Aphid-Susceptible Cultivars of Wheat - Ying Han; Yu Wang; Jian-Long Bi; Xiao-Qin Yang; Yong Huang; Xin Zhao; Yuan Hu; Qing-Nian Cai (Journal of Chemical Ecology, 2009)